2003
DOI: 10.1046/j.1365-2672.2003.02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Staphylococcus aureus by the commensal bacteria of human milk

Abstract: Aims: To study the bacterial diversity in expressed human milk with a focus on detecting bacteria with an antimicrobial activity against Staphylococcus aureus, known as a causative agent of maternal breast infections and neonatal infections. Methods and Results: Random isolates (n ¼ 509) were collected from breast milk samples (n ¼ 40) of healthy lactating women, genotypically identified, and tested for antimicrobial activity against Staph. aureus. Commensal staphylococci (64%) and oral streptococci (30%), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
384
3
19

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(424 citation statements)
references
References 45 publications
18
384
3
19
Order By: Relevance
“…Indeed, S. aureus and S. epidermidis are both common mastitis pathogens, yet in several studies examining the bacterial communities of milk produced by women free from mastitis, the presence of both of these species has been reported (18,22,28). It is therefore of great interest to understand why these species are seemingly harmless commensal organisms at some times and pathogens at others.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, S. aureus and S. epidermidis are both common mastitis pathogens, yet in several studies examining the bacterial communities of milk produced by women free from mastitis, the presence of both of these species has been reported (18,22,28). It is therefore of great interest to understand why these species are seemingly harmless commensal organisms at some times and pathogens at others.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria commonly isolated from this biological fluid include staphylococci, streptococci, lactococci, lactobacilli, and enterococci (6,12). In previous studies, we isolated lactobacillus strains belonging to the species Lactobacillus gasseri, L. fermentum, and L. salivarius from milk of healthy mothers (10,12) and showed that their probiotic potential is similar to that of the strains commonly used in commercial probiotic products (10,14).…”
mentioning
confidence: 95%
“…In previous studies, we isolated lactobacillus strains belonging to the species Lactobacillus gasseri, L. fermentum, and L. salivarius from milk of healthy mothers (10,12) and showed that their probiotic potential is similar to that of the strains commonly used in commercial probiotic products (10,14). It has also been suggested that commensal bacteria isolated from human milk have potential use as bacteriotherapeutic agents for the prevention of breast infections caused by S. aureus (6).…”
mentioning
confidence: 97%
“…A nisin producer strain was isolated twice (L. lactis strains 310 and 2410) at monthly intervals in milk samples from the same donor. Lactic acid bacterial species have previously been found in human milk (6,19), but only one L. lactis strain producing nisin has previously been isolated (6). A reason for this could be that the plating technique and plates used in previous studies led to a lower frequency of isolating nisinproducing L. lactis strains.…”
mentioning
confidence: 99%